1989
DOI: 10.1037/0022-3514.57.5.895
|View full text |Cite
|
Sign up to set email alerts
|

Type A behavior, personality hardiness, and cardiovascular responses to stress.

Abstract: Type A behavior and hardiness were examined as predictors of cardiovascular responses to stress in 68 male undergraduates. Systolic and diastolic blood pressure (SBP and DBP) and heart rate were monitored while subjects performed a difficult mirror-tracing task. Type A assessments based on the Structured Interview, but not those based on the Jenkins Activity Survey, were associated with significantly enhanced SBP and DBP elevations. Hardiness was associated with significantly reduced DBP responsiveness. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 48 publications
8
47
0
3
Order By: Relevance
“…Studies with a variety of occupational groups have found that hardiness operates as a significant moderator or buffer of stress (e.g., Bartone, 1989;Contrada, 1989;Kobasa, Maddi, & Kahn, 1982;Roth, Wiebe, Fillingim, & Shay, 1989;Wiebe, 1991). Hardiness has also been identified as a moderator of combat exposure stress in Gulf War soldiers (Bartone, 1993(Bartone, , 1999a(Bartone, , 2000.…”
Section: Personality Hardinessmentioning
confidence: 99%
“…Studies with a variety of occupational groups have found that hardiness operates as a significant moderator or buffer of stress (e.g., Bartone, 1989;Contrada, 1989;Kobasa, Maddi, & Kahn, 1982;Roth, Wiebe, Fillingim, & Shay, 1989;Wiebe, 1991). Hardiness has also been identified as a moderator of combat exposure stress in Gulf War soldiers (Bartone, 1993(Bartone, , 1999a(Bartone, , 2000.…”
Section: Personality Hardinessmentioning
confidence: 99%
“…Other studies point to hardiness as a significant moderator or buffer of stress (e.g. Contrada, 1989;Kobasa et al, 1982;Roth et al, 1989;Wiebe, 1991). In military groups, hardiness has also been identified as a significant moderator of combat exposure stress in Wartime conditions (Bartone, 1999;Bartone et al, 1989) and during combat training (Florian et al, 1995;Westman, 1990).…”
Section: Personality Hardiness and Leader Developmentmentioning
confidence: 99%
“…In general, we see positive consequences stemming from an identification with other cancer survivors and a tendency to view the self in terms of survivorship. Identification as a survivor should link to internal locus of control and more general feelings of self-esteem (Deimling, Kahana, & Schumacher, 1997), which are themselves associated with increased survival (Contrada, 1989). Identification with other survivors may also enhance preventive measures, such as a healthy lifestyle (Mears, 1997).…”
Section: Tertiary Identitiesmentioning
confidence: 99%